Custodians of the sacred mountains : culture and society in the highlands of Bali - Reuter, Thomas Anton (University of Hawaiʻi Press, 2002)
Annotation Custodians of the Sacred Mountains is the first comprehensive ethnography of the Bali Aga, a large ethnic minority that occupies the island's central highlands. The Bali Aga are popularly viewed as the indigenous counterparts to other Balinese who trace their origin to invaders from the Javanese kingdom of Majapait, who have ruled Bali from the fourteenth century A.D. Although Bali remains one of the most intensely researched localities in the world, the Bali Aga have long been overshadowed by the more exotic courtly culture of the south. A closer analysis of the changing position of the Bali Aga within Balinese society provides a key to understanding the politics and social process of cultural representation in Bali and beyond. The process is marked by a blend of representational competition and cooperation among the Bali Aga themselves, among the Bali Aga and southern Balinese, and later among the island's aristocratic elites and foreign colonizers or scholars, and state authorities. The study of this process raises important issues about the establishment and maintenance of status and power structures at regional, national, and global levels. Custodians of the Sacred Mountains explores the marginalization of the Bali Aga in light of a critical theory of cultural representation and calls for a morally engaged approach to ethnographic research. It proposes an intersubjective and communicative model of human interaction as the foundation for understanding the relative significance of cooperation and competition in the cultural production of knowledge.